SIMULATION AND ANALYSIS OF MATHEMATICAL MODEL OF PV MODULE - SINGH, AMRIT PAL; AHMED, NAFEES (IJRDO - Journal of Electrical And Electronics Engineering, 2015)
The primary aim of the present work is to assess the performance of photovoltaic module. The paper presents the development of a MATLAB/SIMULINK model for the solar PV cell. The simulation of photovoltaic model for obtaining the performance characteristic has also been carried out in this paper. The developed the is the simulated and validated experimentally solar panel . the experimental results obtained , exhibited a good agreement with the simulated data.